DevOps essentials on AWS : continuous integration and continuous delivery with AWS Developer tools (LiveLessons (Indianapolis, Ind.), 2017)
"In DevOps Essentials on AWS Complete Video Course, you'll learn how to automate the infrastructure and deployment pipelines using AWS services and tools so if you're some type of software or DevOps-focused engineer or architect interested in learning how to use AWS Developer Tools to create a full-lifecycle software delivery solution, it's the course for you. The focus of the course is on deployment pipeline architectures and its implementations versus software architectures (for example, monoliths, microservices, FaaS, BaaS, etc.)."--Resource description page